Problematic smartphone use and relations with negative affect, fear of missing out, and fear of negative and positive evaluation. (April 2018) - Wolniewicz, Claire A.; Tiamiyu, Mojisola F.; Weeks, Justin W.; Elhai, Jon D.
Abstract: For many individuals, excessive smartphone use interferes with everyday life. In the present study, we recruited a non-clinical sample of 296 participants for a cross-sectional survey of problematic smartphone use, social and non-social smartphone use, and psychopathology-related constructs including negative affect, fear of negative and positive evaluation, and fear of missing out (FoMO). Results demonstrated that FoMO was most strongly related to both problematic smartphone use and social smartphone use relative to negative affect and fears of negative and positive evaluation, and these relations held when controlling for age and gender. Furthermore, FoMO (cross-sectionally) mediated relations between both fear of negative and positive evaluation with both problematic and social smartphone use. Theoretical implications are considered with regard to developing problematic smartphone use. Highlights: FoMO was most strongly related to problematic and social smartphone use. FoMO mediated relations between fear of evaluation and problematic smartphone use. FoMO mediated relations between fear of evaluation and social smartphone use.